High-performance metal-nitrogen-carbon oxygen reduction electrocatalyst with multi-scale holes as well as preparation method and application of high-performance metal-nitrogen-carbon oxygen reduction electrocatalyst

The preparation of multi-scale pore metal-nitrogen-carbon catalysts through high-temperature puffing solves the problem of slow kinetics of oxygen reduction reactions in zinc-air batteries, and achieves efficient oxygen reduction catalysis, reduces costs, and has the potential to replace precious metal Pt/C catalysts.

CN119742385APending Publication Date: 2025-04-01HUNAN INSTITUTE OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411927318.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The slow kinetics of zinc-air batteries (ZABs) and slow mass transfer lead to low actual energy density, and precious metal Pt/C catalysts are expensive, poor durability and scarce resources.

Method used

By utilizing the high-energy MOFs of triazole to release a large amount of nitrogen "pore-making" properties, high-temperature pyrolysis is used to prepare a metal-nitrogen-carbon (MPFeNi@NC) catalyst with multi-scale pore channels, combining bimetallic active sites and highly nitrogen-doped multi-scale pore carbon networks.

Benefits of technology

The cathode ORR kinetic process of zinc-air fuel cell is significantly improved, the catalytic activity is improved, the catalyst cost is reduced, and the application value of potential replacement of Pt/C catalysts is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742385A_ABST
    Figure CN119742385A_ABST
Patent Text Reader

Abstract

The invention provides a high-performance metal-nitrogen-carbon oxygen reduction electrocatalyst with multi-scale pores and a preparation method and application thereof, and the method comprises the following steps: self-assembling a 1, 2, 3-triazole nitrogen-rich ligand and 3d transition metal ions to generate a micro-nano trimetal high-energy MOF (Metal Organic Framework); and performing high-temperature expansion and two-step pyrolysis to prepare the metal-nitrogen-carbon oxygen reduction electrocatalyst material with high specific surface area and multi-scale pores. The preparation process is simple, the prepared catalyst has multi-scale pore distribution (macropores, mesopores and micropores), large specific surface area (838.46 mg cm <-2 >) and high nitrogen content (4.17 at%), a multi-scale pore carbon network framework can effectively disperse metal alloy nanoparticles, the number of catalytic active sites is increased, the problems of slow ORR kinetics and the like are effectively solved, and the catalyst has good application prospects. And the material has potential application in the aspect of zinc-air fuel cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of oxygen reduction catalysts, and in particular to a high-performance metal-nitrogen-carbon oxygen reduction electrocatalyst with multi-scale pores, a preparation method and an application thereof. Background Art

[0002] Green, low-cost, and high theoretical energy density zinc-air batteries (ZABs) have attracted much attention in “zero-emission” energy conversion and storage devices. However, the slow four-electron kinetics of the oxygen reduction reaction (ORR) on the ZABs air cathode is a key factor limiting the efficiency of ZABs. Therefore, the slow catalytic kinetics and slow mass transfer of ZABs, resulting in low actual energy density, are key technical bottlenecks.

[0003] Precious metal Pt / C catalysts are currently the benchmark ORR electrocatalysts with high activity, but their high price, poor durability and scarce resources seriously hinder their large-scale commercial application. Theoretical "volcano maps" reveal that non-precious metal (such as Fe, Co and Ni) nitrogen co-doped carbon-based materials are the most promising alternatives to replace precious metal Pt-based materials.

[0004] The diffusion of reactants to the active sites through ZABs air electrode catalysts requires a suitable pore structure. The pore size distribution and spatial pore connectivity directly affect the mass transfer characteristics of macroporous catalysts (reactant transfer, ion diffusion and transfer processes). Studies have found that the appropriate pore shape at the open end allows full utilization of the surface area to transport O2, thereby enhancing the transport kinetics. At lower current densities, the narrow / closed ends of the pores hinder mass transfer, resulting in poor kinetic performance and low specific surface area utilization. Generally, micropores (<2nm) can capture oxygen molecules to enhance the interaction with catalytic active centers, mesopores (2-50nm) are considered to be the main reaction space constituting most of the three-phase interfaces, and macropores (>50nm) mainly play a role in enhancing the diffusion of electrolyte mass. Therefore, the pore structure is crucial for efficient three-phase reactions and rapid mass transfer between electrolyte and oxygen molecules.

[0005] Metal-organic framework (MOFs)-derived transition metal-nitrogen-carbon (TM@NC) nanomaterials have been used as the most promising cathode materials for catalyzing ORR in ZABs due to their rich heteroatom doping, highly porous structure, abundant metal active sites and sufficient electrolyte interface area. Although significant progress has been made in the preparation of TM@NC nanomaterials by high-temperature pyrolysis of MOFs as self-sacrificial templates, there are still a series of problems that cannot be ignored, such as the presence of abundant narrow pores (including micropores and small mesopores) in traditional low-nitrogen imidazole / nitrogen-free carboxylic acid MOFs (such as ZIFs and MILs series) derived materials, and the slow mass transfer process in the narrow pores leads to poor accessibility of oxygen to the active sites. In addition, the large loss of nitrogen content during the high-temperature pyrolysis of low-nitrogen / nitrogen-free MOFs is not conducive to the improvement of the intrinsic catalytic activity of the catalyst.

[0006] Therefore, in order to overcome this problem, it is of great significance to develop high-energy nitrogen-containing MOFs constructed by high-temperature expansion and having nitrogen-rich multi-scale pores (macroporous-mesopore-micropore). Summary of the invention

[0007] The present invention provides a high-performance metal-nitrogen-carbon oxygen reduction electrocatalyst with multi-scale pores and a preparation method and application thereof, the purpose of which is to solve the problems of slow ORR kinetics and slow mass transfer of ZABs leading to low actual energy density.

[0008] In order to achieve the above objectives, the embodiments of the present invention provide a high-performance metal-nitrogen-carbon oxygen reduction electrocatalyst with multi-scale pores and its preparation method and application, by utilizing the high-temperature expansion of triazole high-energy MOFs to release a large amount of nitrogen "pore-forming" characteristics, high-temperature pyrolysis to prepare metal-nitrogen-carbon (MPFeNi@NC) materials with multi-scale pore channels. Specifically, the three metal ions (Zn 2+ / Fe 2+ / Ni 2+ ) and nitrogen-rich 1H-1,2,3-triazole (C2H3N3, 60wt% N) ligands self-assembled to generate a high-energy nitrogen-containing MOF (EMOF, i.e., MET-6(FeNiZn)). During the pyrolysis process under an inert atmosphere, the high-energy nitrogen-containing ligand (1,2,3-triazole) acts as a carbon source and a nitrogen source, and decomposes at high temperature to release a large amount of nitrogen. The energy accumulates and explodes to form a highly nitrogen-doped multi-scale porous carbon network. At the same time, the metal Zn 2+ It is easily reduced to Zn at high temperature and evaporates at high temperature (low boiling point: 907℃); metal Fe 2 + / Ni 2+The ions are easily reduced to FeNi alloy at high temperature, but due to their high boiling points (Fe: 2750°C, Ni: 2732°C), the FeNi alloy is eventually evenly embedded in the carbon matrix. 2 g -1 ) and high nitrogen doping (4.17 at %), the synthesized high-performance MPFeNi@NC catalyst exhibits excellent ORR catalytic activity (E 1 / 2 =0.895V). The present invention aims to solve the problems of slow ORR kinetics and slow mass transfer rate of ZABs air electrode catalysts by constructing multi-scale pores and introducing bimetallic active sites in MPFeNi@NC catalysts, breaking through the key technical bottleneck of low actual energy density of ZABs, and is expected to prepare a new catalyst that can replace Pt / C.

[0009] An object of an embodiment of the present invention is to provide a method for preparing a high-performance multi-scale porous metal-nitrogen-carbon oxygen reduction electrocatalyst, comprising the following steps:

[0010] (1) Weighing zinc salt, iron salt and nickel salt, adding them to a mixed solvent of N,N-dimethylformamide, ethanol, water and ammonia water, uniformly dispersing by ultrasonication, and slowly stirring at room temperature to obtain a mixed solution;

[0011] (2) measuring 1,2,3-triazole nitrogen-rich ligand and slowly dropping it into the mixed solution, and continuously stirring at room temperature;

[0012] (3) centrifugally separating the product obtained after stirring in step (2), washing the separated reaction product with ultrapure water and ethanol until neutral, and fully drying to obtain a MET-6 precursor;

[0013] (4) The MET-6 precursor is placed in a tube furnace and pyrolyzed in two steps under an inert atmosphere to prepare MPFeNi@NC.

[0014] Preferably, in step (1), the zinc salt is at least one of zinc nitrate hexahydrate, zinc sulfate, zinc chloride, and zinc acetate; the iron salt is at least one of ferric nitrate nonahydrate, ferric chloride hexahydrate, ammonium ferrous sulfate hexahydrate, ferrous sulfate, ferrous sulfate, ferrous chloride tetrahydrate, ferrous acetate tetrahydrate, anhydrous ferrous chloride, and anhydrous ferric chloride; and the nickel salt is at least one of nickel chloride hexahydrate and nickel sulfate; wherein the concentration of the zinc salt is 16-18 mM, the concentration of the iron salt is 2-3 mM, and the concentration of the nickel salt is 2-3 mM; and the volume ratio of N,N-dimethylformamide, ethanol, water, and ammonia water in the mixed solvent is 2:2:3:1. More preferably, the concentration of ZnCl2 is 17.8 mM; the concentration of FeCl2·4H2O is 2.7 mM; and the concentration of NiCl2·6H2O is 2.7 mM. More preferably, the volumes of N,N-dimethylformamide, ethanol, water and aqueous ammonia are 20 mL: 20 mL: 30 mL: 10 mL.

[0015] Preferably, in step (1), the ultrasonication time is 20 to 30 minutes.

[0016] Preferably, in step (2), the molar ratio of zinc salt, iron salt and nickel salt is 97:1.5:1.5, and the molar ratio of the sum of zinc salt, iron salt and nickel salt to 1,2,3-triazole is 1:2-5; the nitrogen content in the 1,2,3-triazole is 60.8wt.%.

[0017] Preferably, in step (2), the stirring time is 10 to 14 hours.

[0018] Preferably, in step (3), the drying temperature is 60°C.

[0019] Preferably, in step (4), the inert atmosphere is nitrogen; the first step pyrolysis temperature is 200°C, and the insulation time is 1 to 3 hours; the second step pyrolysis temperature is 800 to 1000°C, and the insulation time is 1 to 3 hours.

[0020] Based on an overall concept of the invention, an embodiment of the present invention provides a high-performance metal-nitrogen-carbon oxygen reduction electrocatalyst with multi-scale pores prepared by the above-mentioned preparation method.

[0021] Preferably, the multi-scale pores in the metal-nitrogen-carbon oxygen reduction electrocatalyst include macropores, mesopores and micropores; the specific surface area is as high as 838.46 mg cm -2 ; Nitrogen content up to 4.17at%; Half-wave potential: E 1 / 2 =0.895V.

[0022] Another object of an embodiment of the present invention is to provide the application of the above-mentioned high-performance multi-scale porous metal-nitrogen-carbon oxygen reduction electrocatalyst as a catalytic material in a fuel cell or a metal-air battery.

[0023] mechanism

[0024] The present invention self-assembles 1,2,3-triazole nitrogen-rich ligands and 3d transition metal ions to generate micro-nano trimetallic high-energy MOF; wherein, the self-assembly method is a coprecipitation method, and a large amount of MET-6 (ZnFeNi) can be self-assembled by slowly stirring at room temperature for a period of time; and then high-temperature expansion and two-step pyrolysis are performed to prepare a metal-nitrogen-carbon oxygen reduction electrocatalyst material with a high specific surface area and multi-scale pores; and after the MET-6 (ZnFeNi) precursor is pyrolyzed at high temperature, the metal zinc evaporates, and the metal iron and nickel are uniformly embedded in the multi-scale porous carbon network in the form of an alloy. The multi-scale porous carbon network framework can effectively disperse metal alloy nanoparticles, increase the number of catalytic active sites, and effectively solve the problem of slow ORR kinetics. The MPFeNi@NC synthesized by this method has a bimetallic active site (iron-nickel alloy) and a high nitrogen content (4.17at%), which is conducive to the formation of the key active site (FeNi@NC) of ORR, and has potential applications in zinc-air fuel cells.

[0025] The above scheme of the present invention has the following beneficial effects:

[0026] (1) The present invention utilizes the "pore-forming" property of high-energy nitrogen-containing ligands of triazole to expand at high temperature and release a large amount of nitrogen. The MPFeNi@NC catalyst with multi-scale pore channels is prepared by high-temperature pyrolysis of 3d transition metal triazole high-energy MOFs. The active bimetallic alloy can serve as the ORR active center to promote the oxygen catalytic process, and the nitrogen atom-doped multi-scale porous carbon network can effectively prevent the further aggregation of metal alloy particles. Based on the highly active bimetallic FeNi alloy and multi-scale pore structure, the MPFeNi@NC catalyst can significantly improve the cathode ORR kinetics of zinc-air fuel cells.

[0027] (2) Inexpensive 3d transition metal iron and nickel are selected as efficient active metal sites, and the multi-scale porous carbon skeleton retained after pyrolysis of the nitrogen-rich MET-6 (ZnFeNi) framework is used as a carbon carrier. The active metals are loaded on the carbon carrier to form a high-performance oxygen reduction MPFeNi@NC with multi-scale pores to replace the traditional precious metal Pt / C catalyst, which greatly reduces the cost of zinc-air fuel cell catalysts and improves market competitiveness. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1 Schematic diagram of the synthesis method of MPFeNi@NC oxygen reduction catalyst in one embodiment of the present invention.

[0030] Figure 2 1 is the XRD diagram of the MET-6 (ZnFeNi) precursor and the MPFeNi@NC catalyst according to one embodiment of the present invention, a is the MET-6 (ZnFeNi) precursor, and b is the MPFeNi@NC catalyst.

[0031] Figure 3 The SEM (a) and TEM images (b) of the MPFeNi@NC catalyst obtained in one embodiment of the present invention.

[0032] Figure 4 The SEM and mapping images of the MPFeNi@NC catalyst prepared in one embodiment of the present invention.

[0033] Figure 5 These are the adsorption-desorption curve and pore size distribution diagram of the MPFeNi@NC catalyst prepared in one embodiment of the present invention, where a is the adsorption-desorption curve and b is the pore size distribution diagram.

[0034] Figure 6 : is the LSV curve diagram of MPFeNi@NC obtained in one embodiment of the present invention. DETAILED DESCRIPTION

[0035] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.

[0036] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0037] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0038] In the “MPFeNi@NC” mentioned below, “MP” specifically refers to porous.

[0039] The existing ZABs have problems such as slow ORR kinetics and slow mass transfer, which lead to low actual energy density.

[0040] An object of an embodiment of the present invention is to provide a method for preparing a high-performance multi-scale porous metal-nitrogen-carbon oxygen reduction electrocatalyst, comprising the following steps:

[0041] (1) Weighing zinc salt, iron salt and nickel salt, adding them to a mixed solvent of N,N-dimethylformamide, ethanol, water and ammonia water, uniformly dispersing by ultrasonication, and slowly stirring at room temperature to obtain a mixed solution;

[0042] (2) measuring 1,2,3-triazole nitrogen-rich ligand and slowly dropping it into the mixed solution, and continuously stirring at room temperature;

[0043] (3) centrifugally separating the product obtained after stirring in step (2), washing the separated reaction product with ultrapure water and ethanol until neutral, and fully drying to obtain a MET-6 precursor;

[0044] (4) The MET-6 precursor is placed in a tube furnace and pyrolyzed in two steps under an inert atmosphere to prepare MPFeNi@NC.

[0045] Preferably, in step (1), the zinc salt is at least one of zinc nitrate hexahydrate, zinc sulfate, zinc chloride, and zinc acetate; the iron salt is at least one of ferric nitrate nonahydrate, ferric chloride hexahydrate, ammonium ferrous sulfate hexahydrate, ferrous sulfate, ferrous sulfate, ferrous chloride tetrahydrate, ferrous acetate tetrahydrate, anhydrous ferrous chloride, and anhydrous ferric chloride; and the nickel salt is at least one of nickel chloride hexahydrate and nickel sulfate; wherein the concentration of the zinc salt is 16-18 mM, the concentration of the iron salt is 2-3 mM, and the concentration of the nickel salt is 2-3 mM; and the volume ratio of N,N-dimethylformamide, ethanol, water, and aqueous ammonia in the mixed solvent is 2:2:3:1.

[0046] Preferably, in step (1), the ultrasonication time is 20 to 30 minutes.

[0047] Preferably, in step (2), the molar ratio of zinc salt, iron salt and nickel salt is 97:1.5:1.5, and the molar ratio of the sum of zinc salt, iron salt and nickel salt to 1,2,3-triazole is 1:2-5; the nitrogen content in the 1,2,3-triazole is 60.8wt.%.

[0048] Preferably, in step (2), the stirring time is 10 to 14 hours.

[0049] Preferably, in step (3), the drying temperature is 60°C.

[0050] Preferably, in step (4), the inert atmosphere is nitrogen; the first step pyrolysis temperature is 200°C, and the insulation time is 1 to 3 hours; the second step pyrolysis temperature is 800 to 1000°C, and the insulation time is 1 to 3 hours.

[0051] Based on an overall concept of the invention, an embodiment of the present invention provides a high-performance metal-nitrogen-carbon oxygen reduction electrocatalyst with multi-scale pores prepared by the above-mentioned preparation method.

[0052] Preferably, the multi-scale pores in the metal-nitrogen-carbon oxygen reduction electrocatalyst include macropores, mesopores and micropores; the specific surface area is as high as 838.46 mg cm -2 ; Nitrogen content up to 4.17at%; Half-wave potential: E 1 / 2 =0.895V.

[0053] Another object of an embodiment of the present invention is to provide the application of the above-mentioned high-performance multi-scale porous metal-nitrogen-carbon oxygen reduction electrocatalyst as a catalytic material in a fuel cell or a metal-air battery.

[0054] The advantages of the above technical solution compared with the existing technology are as follows:

[0055] (1) The present invention utilizes the "pore-forming" property of high-energy nitrogen-containing ligands of triazole to expand at high temperature and release a large amount of nitrogen. The MPFeNi@NC catalyst with multi-scale pore channels is prepared by high-temperature pyrolysis of 3d transition metal triazole high-energy MOFs. The active bimetallic alloy can serve as the ORR active center to promote the oxygen catalytic process, and the nitrogen atom-doped multi-scale porous carbon network can effectively prevent the further aggregation of metal alloy particles. Based on the highly active bimetallic FeNi alloy and multi-scale pore structure, the MPFeNi@NC catalyst can significantly improve the cathode ORR kinetics of zinc-air fuel cells.

[0056] (2) Inexpensive 3d transition metal iron and nickel are selected as efficient active metal sites, and the multi-scale porous carbon skeleton retained after pyrolysis of the nitrogen-rich MET-6 (ZnFeNi) framework is used as a carbon carrier. The active metals are loaded on the carbon carrier to form a high-performance oxygen reduction MPFeNi@NC with multi-scale pores to replace the traditional precious metal Pt / C catalyst, which greatly reduces the cost of zinc-air fuel cell catalysts and improves market competitiveness.

[0057] The following is a detailed description through specific embodiments.

[0058] Example 1

[0059] A method for preparing a high-performance metal-nitrogen-carbon oxygen reduction electrocatalyst with multi-scale pores comprises the following steps:

[0060] (1) Weigh 1.94 g (14.24 mmol) ZnCl2, 43.78 mg (0.22 mmol) FeCl2·4H2O and 52.34 mg (0.22 mmol) NiCl2·6H2O, add them to a mixed solvent of 20 mL N,N-dimethylformamide, 20 mL ethanol, 30 mL water and 10 mL ammonia water, ultrasonicate for 20 to 30 min to disperse them evenly, and stir slowly at room temperature;

[0061] (2) taking 2.5 mL of 1,2,3-triazole nitrogen-rich ligand and slowly dropping it into the mixed solution of step (1), and continuously stirring at room temperature for 10 to 12 hours;

[0062] (3) After stirring at room temperature, the product obtained in step (2) is placed in a centrifuge tube and centrifuged to separate the reactants, and the reactants are washed with ultrapure water and ethanol until neutral, and fully dried at 60° C. to obtain a MET-6 (ZnFeNi) precursor solid sample;

[0063] (4) The MET-6 (ZnFeNi) precursor obtained in step (3) was placed in a magnetic boat, and placed in a tube furnace, and nitrogen was introduced at 5 ° C min -1 The sample was thermally annealed at a lower temperature (T1 = 200 °C) for 2 h at a heating rate, and then the temperature was further increased to a higher temperature (T2 = 900 °C) and kept at this temperature for another 2 h, and then cooled to 25 °C in a nitrogen inert environment to obtain MPFeNi@NC.

[0064] Example 2

[0065] A method for preparing a high-performance metal-nitrogen-carbon oxygen reduction electrocatalyst with multi-scale pores comprises the following steps:

[0066] (1) Weigh 1.92 g (14.097 mmol) ZnCl2, 43.34 mg (0.218 mmol) FeCl2·4H2O and 51.82 mg (0.218 mmol) NiCl2·6H2O, add them to a mixed solvent of 20 mL N,N-dimethylformamide, 20 mL ethanol, 30 mL water and 10 mL ammonia water, ultrasonically disperse them for 20 to 30 min, and slowly stir them at room temperature;

[0067] (2) taking 2.5 mL of 1,2,3-triazole nitrogen-rich ligand and slowly dropping it into the mixed solution of step (1), and continuously stirring at room temperature for 10 to 12 hours;

[0068] (3) After stirring at room temperature, the product obtained in step (2) is placed in a centrifuge tube and centrifuged to separate the reactants, and the reactants are washed with ultrapure water and ethanol until neutral, and fully dried at 60° C. to obtain a MET-6 (ZnFeNi) solid sample;

[0069] (4) The MET-6 (ZnFeNi) precursor obtained in step (3) was placed in a magnetic boat, and placed in a tube furnace, and nitrogen was introduced at 5 ° C min -1 The sample was thermally annealed at a lower temperature (T1 = 200 °C) for 2 h at a heating rate, and then the temperature was further increased to a higher temperature (T2 = 800) and kept for another 2 h, and then cooled to 25 °C in a nitrogen inert environment to obtain MPFeNi@NC.

[0070] Example 3

[0071] A method for preparing a high-performance metal-nitrogen-carbon oxygen reduction electrocatalyst with multi-scale pores comprises the following steps:

[0072] (1) Weigh 1.96 g (14.38 mmol) ZnCl2, 44.22 mg (0.222 mmol) FeCl2·4H2O and 52.86 mg (0.222 mmol) NiCl2·6H2O, add them to a mixed solvent of 20 mL N,N-dimethylformamide, 20 mL ethanol, 30 mL water and 10 mL ammonia water, ultrasonically disperse them for 20 to 30 min, and slowly stir them at room temperature;

[0073] (2) taking 2.5 mL of 1,2,3-triazole nitrogen-rich ligand and slowly dropping it into the mixed solution of step (1), and continuously stirring at room temperature for 10 to 12 hours;

[0074] (3) After stirring at room temperature, the product obtained in step (2) is placed in a centrifuge tube and centrifuged to separate the reactants, and the reactants are washed with ultrapure water and ethanol until neutral, and fully dried at 60° C. to obtain a MET-6 (ZnFeNi) solid sample;

[0075] (4) The MET-6 (ZnFeNi) precursor obtained in step (3) was placed in a magnetic boat, and placed in a tube furnace, and nitrogen was introduced at 5 ° C min -1 The sample was thermally annealed at a lower temperature (T1 = 200 °C) for 2 h at a heating rate, and then the temperature was further increased to a higher temperature (T2 = 1000 °C) and maintained for another 2 h, and then cooled to 25 °C in a nitrogen inert environment to obtain MPFeNi@NC.

[0076] Comparative Example 1

[0077] Commercial Pt / C (20%) was used as the ORR catalyst.

[0078] Comparative Example 2

[0079] The method of Example 1 is followed, except that NiCl2·6H2O is not added in the preparation of the mixed solution in step (1).

[0080] Comparative Example 3

[0081] The method of Example 1 is followed, except that in step (1), NiCl2·6H2O is replaced by CoCl2 to prepare a mixed solution.

[0082] Comparative Example 4

[0083] The method of Example 1 is followed, except that CuCl2 is added in the preparation of step (1) to prepare a mixed solution.

[0084] Comparative Example 5

[0085] The method of Example 1 is followed, except that in the preparation of step (2), the nitrogen-rich 1,2,3-triazole is replaced by 4,4',4"-tris(1,2,4-triazol-4-yl)triphenylamine.

[0086] Comparative Example 6

[0087] The method of Example 1 is followed, except that benzimidazole is further added in the preparation of step (2).

[0088] Comparative Example 7

[0089] The method of Example 1 is followed, except that in the preparation of step (1), n(ZnCl2):n(FeCl2·4H2O):n(NiCl2·6H2O) is set to 96:2:2.

[0090] Comparative Example 8

[0091] The method of Example 1 is followed, except that in the preparation of step (1), n(ZnCl2):n(FeCl2·4H2O):n(NiCl2·6H2O) is set to 98:0.5:0.5.

[0092] Comparative Example 9

[0093] The method of Example 1 is followed, except that T2 is set to 800° C. in the preparation of step (4).

[0094] Comparative Example 10

[0095] The method of Example 1 is followed, except that T2 is set to 1000° C. in the preparation of step (4).

[0096] The evaluation method of the catalytic performance of the above comparative examples 1 to 10 is the same as that of Example 1. Structural characterization and ORR performance study of MPFeNi@NC prepared in the example:

[0097] (1) Structural characterization of the MPFeNi@NC catalyst prepared in Example:

[0098] The prepared MET-6(ZnFeNi) and MPFeNi@NC were characterized by D8 Advance X-ray diffractometer (XRD) and compared with the standard peaks of FeNi alloy standard cards. Figure 2 shown.

[0099] The morphology and pore structure of MPFeNi@NC were characterized by JEM-2800 transmission electron microscope and S-4800 scanning electron microscope. Figure 3 shown.

[0100] The morphology and element distribution of MPFeNi@NC were characterized by S-4800 scanning electron microscope. Figure 4 shown.

[0101] The specific surface area and pore size distribution of the material were measured using the ASAP2020 specific surface area and porosity tester. The test method was to first degas at 120°C for 12 hours and then transfer to the instrument for testing. The results are as follows: Figure 5 shown.

[0102] (2) ORR performance test of MPFeNi@NC catalyst:

[0103] The ORR performance of MPFeNi@NC was tested using a CHI 760E electrochemical workstation and a rotating ring disk electrode. A three-electrode system was used, with a glassy carbon electrode as the working electrode, a graphite rod as the counter electrode, an Ag / AgCl electrode as the reference electrode, and 0.1M potassium hydroxide as the electrolyte. The glassy carbon electrode used MPFeNi@NC as a catalyst, which was dispersed in the solution and evenly covered on the surface of the glassy carbon electrode and dried naturally. The LSV curve of MPFeNi@NC was measured as follows: Figure 6 MPFeNi@NC catalyst is better than commercial Pt / C(E onset =0.96V, E 1 / 2 =0.835 V) shows a higher onset potential (E onset =0.98V) and higher half-wave potential (E 1 / 2 =0.895V).

[0104] Compared with commercial Pt / C (Comparative Example 1, E 1 / 2 = 0.835V), single metal site such as nickel-nitrogen-carbon (Comparative Example 2, E 1 / 2 = 0.815V), dual metal sites such as cobalt iron-nitrogen-carbon (Comparative Example 3, E 1 / 2 =0.885V), trimetallic sites such as nickel-iron-copper-nitrogen-carbon (Comparative Example 4, E 1 / 2 =0.855V), other nitrogen-containing ligands (Comparative Example 5, E 1 / 2 =0.875V), double nitrogen-containing ligand (Comparative Example 6, E 1 / 2 =0.885V), parameter control such as raw material ratio (Comparative Example 7, E 1 / 2 =0.865V; Comparative Example 8, E 1 / 2 =0.875V), parameter control such as pyrolysis temperature (Comparative Example 9, E 1 / 2 =0.835V; Comparative Example 10, E 1 / 2=0.845V), the bimetallic MPFeNi@NC oxygen reduction electrocatalyst obtained in the embodiment has incomparable advantages, not only constructing multi-scale pores (macroporous, mesopores and micropores), but also having a high specific surface area (838.46mg cm -2 ); high nitrogen content (4.17 at%), ultimately showing the best activity in ORR with the highest half-wave potential (E 1 / 2 =0.895V), and the required ligand is cheap and low in cost.

[0105] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a high-performance multi-scale porous metal-nitrogen-carbon oxygen reduction electrocatalyst, characterized in that: The following steps are involved: (1) Weighing zinc salt, iron salt and nickel salt, adding them to a mixed solvent of N,N-dimethylformamide, ethanol, water and ammonia water, uniformly dispersing by ultrasonication, and slowly stirring at room temperature to obtain a mixed solution; (2) measuring 1,2,3-triazole nitrogen-rich ligand and slowly dropping it into the mixed solution, and continuously stirring at room temperature; (3) centrifugally separating the product obtained after stirring in step (2), washing the separated reaction product with ultrapure water and ethanol until neutral, and fully drying to obtain a MET-6 precursor; (4) The MET-6 precursor is placed in a tube furnace and pyrolyzed in two steps under an inert atmosphere to prepare MPFeNi@NC.

2. The method for preparing a high-performance multi-scale porous metal-nitrogen-carbon oxygen reduction electrocatalyst according to claim 1, characterized in that: In step (1), the zinc salt is at least one of zinc nitrate hexahydrate, zinc sulfate, zinc chloride, and zinc acetate; the iron salt is at least one of ferric nitrate nonahydrate, ferric chloride hexahydrate, ammonium ferrous sulfate hexahydrate, ferrous sulfate, ferrous sulfate, ferrous chloride tetrahydrate, ferrous acetate tetrahydrate, anhydrous ferrous chloride, and anhydrous ferric chloride; and the nickel salt is at least one of nickel chloride hexahydrate and nickel sulfate; wherein the concentration of the zinc salt is 16-18 mM, the concentration of the iron salt is 2-3 mM, and the concentration of the nickel salt is 2-3 mM; and the volume ratio of N,N-dimethylformamide, ethanol, water, and aqueous ammonia in the mixed solvent is 2:2:3:

1.

3. The method for preparing a high-performance multi-scale porous metal-nitrogen-carbon oxygen reduction electrocatalyst according to claim 1, characterized in that: In step (1), the ultrasonic treatment time is 20 to 30 minutes.

4. The method for preparing a high-performance multi-scale porous metal-nitrogen-carbon oxygen reduction electrocatalyst according to claim 1, characterized in that: In step (2), the molar ratio of zinc salt, iron salt and nickel salt is 97:1.5:1.5, and the molar ratio of the sum of zinc salt, iron salt and nickel salt to 1,2,3-triazole is 1:2-5; the nitrogen content in the 1,2,3-triazole is 60.8wt.%.

5. The method for preparing a high-performance multi-scale porous metal-nitrogen-carbon oxygen reduction electrocatalyst according to claim 1, characterized in that: In step (2), the stirring time is 10 to 14 hours.

6. The method for preparing a high-performance multi-scale porous metal-nitrogen-carbon oxygen reduction electrocatalyst according to claim 1, characterized in that: In step (3), the drying temperature is 60°C.

7. The method for preparing a high-performance multi-scale porous metal-nitrogen-carbon oxygen reduction electrocatalyst according to claim 1, characterized in that: In step (4), the inert atmosphere is nitrogen; the first step pyrolysis temperature is 200°C, and the insulation time is 1 to 3 hours; the second step pyrolysis temperature is 800 to 1000°C, and the insulation time is 1 to 3 hours.

8. A high-performance multi-scale porous metal-nitrogen-carbon oxygen reduction electrocatalyst prepared by the preparation method according to any one of claims 1 to 7.

9. The high performance multi-scale porous metal-nitrogen-carbon oxygen reduction electrocatalyst according to claim 8, characterized in that: The multi-scale pores in the metal-nitrogen-carbon oxygen reduction electrocatalyst include macropores, mesopores and micropores; the specific surface area is as high as 838.46 mg cm -2 ; Nitrogen content up to 4.17at%; Half-wave potential: E 1 / 2 =0.895V.

10. Use of the high-performance multi-scale porous metal-nitrogen-carbon oxygen reduction electrocatalyst as claimed in claim 8 as a catalytic material in a fuel cell or a metal-air battery.